2020
DOI: 10.1101/2020.04.20.052332
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Thermodynamic Interpretation of the Stimulated Raman Spectroscopic Signature of an Action Potential in a Single Neuron

Abstract: It has previously been suggested that the plasma membrane condenses and melts reversibly during an action potential in a neuron. If true it has fundamental consequences for our understanding of the regulation of biological functions during an action potential. It has long been known that the electrical dipoles in the neuronal membrane reorient during an action potential, observed through a variety of optical methods. However, this information has been insufficient to confirm if and how the collective thermodyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Indeed, Tasaki has measured changes in the emission spectra of solvatochromic dyes in nerves during an action potential and he showed that the spectral width decreases (Tasaki et al, 1973), and hence it can now be claimed the membrane stiffness increases during an action potential per eq.17. Recently, an attempt was made to perform similar measurements based in changes in the Raman spectra of single neurons (Shrivastava et al, 2020). Similar measurements under a range of physico-chemical conditions and excitable systems, as outlined by others (Fillafer et al, 2019;Fillafer and Schneider, 2015;Wang et al, 2018), will lead to the required clarity on the mechanisms of nerve pulse propagation.…”
Section: Falsification Criteria and The Role Of Optical Methodsmentioning
confidence: 92%
“…Indeed, Tasaki has measured changes in the emission spectra of solvatochromic dyes in nerves during an action potential and he showed that the spectral width decreases (Tasaki et al, 1973), and hence it can now be claimed the membrane stiffness increases during an action potential per eq.17. Recently, an attempt was made to perform similar measurements based in changes in the Raman spectra of single neurons (Shrivastava et al, 2020). Similar measurements under a range of physico-chemical conditions and excitable systems, as outlined by others (Fillafer et al, 2019;Fillafer and Schneider, 2015;Wang et al, 2018), will lead to the required clarity on the mechanisms of nerve pulse propagation.…”
Section: Falsification Criteria and The Role Of Optical Methodsmentioning
confidence: 92%
“…Given that the evidence of a increased order and compression was recently presented for an action potential in a single neuron (55), and an undisputable role of mechanics in neuronal signal transduction (56), the physical insights provided by the above mechanism for collision need to be investigated during the collision or interaction of waves in neurons. In general, excitation waves from propagating graded potentials to action-potential, show an entire range of interactions; from superposition to supra-linear, to sublinear summation (57).…”
Section: Discussionmentioning
confidence: 99%